Penerapan Model Make A Match Berbantuan Media Permainan Ular Tangga Untuk Meningkatkan Hasil Belajar Siswa - Adelina Noorisa; Erik Aditia Ismaya; Mila Roysa (Journal on Education, 2020)
The study aims to improve student learning outcomes in sloving problems with the material by implementing the Make A Match model assisted by snake and ladder media. The subjects of this study were 26 grade IV students with the location of the research carried out in SD 1 Gamong, Kaliwungu District, Kudus Regency. This research lasted for 2 cycles with 2 meatings in each cycle. Data collection techniques are carried out in the form of test and observation sheets.Beston the results of the analysis obtained, it shows that the application of the Make A Match model with the assistance of snake and ladder media on theme 7 especially in social studies content and indonesian can improve student learning outcomes. This research is expected that other researchers can develop learning using the Make A Match model to be more effective by paying more attention to learning syntax and paying attention to the characteristics of the subjects and materials to be used.